2015
DOI: 10.3390/md13020713
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Antimicrobial Potential of Bromoditerpenes Isolated from the Red Alga, Sphaerococcus coronopifolius

Abstract: Cancer and infectious diseases continue to be a major public health problem, and new drugs are necessary. As marine organisms are well known to provide a wide range of original compounds, the aim of this study was to investigate the bioactivity of the main constituents of the cosmopolitan red alga, Sphaerococcus coronopifolius. The structure of several bromoditerpenes was determined by extensive spectroscopic analysis and comparison with literature data. Five molecules were isolated and characterized which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 41 publications
0
40
0
2
Order By: Relevance
“…Still. mainly the terpernoids found in red seaweeds have demonstrated a high antitumor bioactivity [8,[54][55][56]. Most of terpenoids with the variation in their structures are biologically active and are used worldwide for illnesses treatment [41].…”
Section: Terpenesmentioning
confidence: 99%
“…Still. mainly the terpernoids found in red seaweeds have demonstrated a high antitumor bioactivity [8,[54][55][56]. Most of terpenoids with the variation in their structures are biologically active and are used worldwide for illnesses treatment [41].…”
Section: Terpenesmentioning
confidence: 99%
“…Red [101] Callophycus serratus Diterpene-benzoate Red [98] Antibacterial activity is expressed across multiple mechanisms: inhibition of oxidative phosphorylation and link with compounds in the bacterial cell wall and increased permeability of the cytoplasmic membrane causing cell lysis [97]. At the same time some seaweed compounds, in particular polysaccharides, contribute significantly to the health and well-being of the animals by enhancing the in vivo immune response.…”
Section: Sphaerane Bromoditerpenesmentioning
confidence: 99%
“…Previous studies carried out with extracts from the red algae S. coronopifolius showed that it possesses several biological effects, such as antioxidant, antimicrobial, antitumor and antiviral potential due to the presence of active secondary metabolites 10,11,12 . Furthermore, the effect of S. coronopifolius phenolic extracts on anxiety-like behavior in female Wistar rats was attempted 13 .…”
mentioning
confidence: 99%